Relationship Between Nursing Students' Awareness of Disaster, Preparedness for Disaster, Willingness to Participate in Disaster Response, and Disaster Nursing Competency. (10th October 2023) - Kang, Ji-Suk; Lee, Hyejin; Seo, Ji Min
Abstract: Objective: This study was conducted to provide basic data for preparing a disaster nursing education program. It examined the degree of nursing students' disaster awareness, disaster preparedness, willingness to participate in disaster response, and disaster nursing competency, aiming to determine the relationship between these attributes. Methods: This was a descriptive research study. The participants were 163 nursing students. The data collected from the participants were analyzed via descriptive statistics and Pearson's correlation coefficients. Results: Disaster awareness showed a positive correlation with a willingness to participate in a disaster response. Further, disaster preparedness and willingness to participate in a disaster response showed a positive correlation with disaster nursing capacity. Disaster awareness did not show a significant correlation with disaster preparedness and disaster nursing competency. Last, disaster preparedness did not show a significant correlation with willingness to participate in a disaster response. Conclusions: It is necessary to improve nursing students' disaster awareness, disaster preparation, disaster response participation willingness, and disaster nursing competency. It is imperative to develop disaster nursing education programs to strengthen students' capabilities in a comprehensive manner.